Political communication a new introduction for crisis times - Davis, Aeron (Cambridge, UK Medford, MA Polity, 2019)
"We are living in a period of great uncertainty, in which many long-predicted tipping points in media and politics have been reached. Aeron Davis bridges old and new to map the shifts and analyse what they mean for our aging democracies. This important book both introduces and challenges the established literature"-- Provided by publisher.
Evaluating democratic politics and communication -- Political communication and crisis in established democracies -- Political parties and elections -- Political reporting and the future of (fake) news -- Media-source relations, mediatization and populist politics -- Citizens, media effects and public participation -- Organised interests, power and the policy process -- Economics, the economy and media -- Digital media and online political communication -- Globalisation, the state and international political communication -- Conclusions : post-truth, post-public sphere and post-democracy.
Includes bibliographical references and index.
Keywords: Communication in politics; Mass media -- Political aspects